2002
DOI: 10.1002/pros.10141
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of orthotopic growth and metastasis of androgen‐sensitive human prostate tumors in mice by bioactive soybean components

Abstract: BACKGROUND-Systematic analysis of the influence of diet on the initiation and progression of prostate cancer is often difficult in human populations, for which dietary variables overlap a diversity of genetic backgrounds and social behaviors. Animal models that emulate human prostate cancer allow experimental analysis of the mechanisms of action of nutritional agents that show anti-prostate cancer activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
69
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 25 publications
3
69
0
Order By: Relevance
“…15,[21][22][23][24] Feeding mice with soy phytochemical concentrate (SPC, containing genistein, daidzein and glycitein) or an aglycone isoflavone preparation reduced tumor growth of s.c. implanted human LNCaP cells in immunocompromised mice. 15,22 In a prevention study of Zhou et al, 23 using an orthotopic model of LNCaP cells in SCID mice similar to our model, SPC was more effective than genistein or soy protein. This prevention study is in agreement with the efficacy demonstrated by soy isoflavones in our therapeutic study of established prostate tumors.…”
Section: Discussionmentioning
confidence: 99%
“…15,[21][22][23][24] Feeding mice with soy phytochemical concentrate (SPC, containing genistein, daidzein and glycitein) or an aglycone isoflavone preparation reduced tumor growth of s.c. implanted human LNCaP cells in immunocompromised mice. 15,22 In a prevention study of Zhou et al, 23 using an orthotopic model of LNCaP cells in SCID mice similar to our model, SPC was more effective than genistein or soy protein. This prevention study is in agreement with the efficacy demonstrated by soy isoflavones in our therapeutic study of established prostate tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Growth inhibition and induction of apoptosis of prostate cancer cells by isoflavones were indicated in several experimental reports. [16][17][18][19][20][21][22][23][24][25] Tofu and natto are rich in isoflavones (tofu 509 µg/g and natto 1273 µg/g 26) ). In fact, Japanese have higher phytoestrogen concentrations in serum than men and women of Western countries (for example, the mean concentration of genistein in phytoestrogen in Japanese men is 492.7 nmol/liter, compared with 33.2 nmol/liter in men from the UK), 27) and have very high urinary excretion of phytoestrogens.…”
Section: Discussionmentioning
confidence: 99%
“…The use of soy in Asian diets is theorized to be one of the reasons for the low incidence and mortality rates from prostate cancer in Asian men, which are rapidly increasing with the Westernization 60 of their traditional diet (17). This hypothesis is supported by findings from both laboratory and animal studies, indicating an anti-proliferative and apoptotic effect in cancer cells of isoflavones, the phytoestrogens present in soy (18)(19)(20)(21). However, epidemiological and clinical investigations on the 65 role of soy protein in relation to IGF-I suggest that soy protein may alter the IGF axis toward an increase in IGF-1 and a reduction in IGFBP-3 (22)(23)(24)(25)(26).…”
Section: Protein (58 G/day) After One Year Intervention Group Patiementioning
confidence: 99%
“…In addition, the correlations performed at one year confirmed the positive association between IGFBP-1 405 and vegetable protein, and also showed a positive association with soy isoflavones. Furthermore, both vegetable protein and soy isoflavones were inversely related to LNCaP cell growth, suggesting that consumption of vegetable protein and isoflavones may be beneficial against tumor growth (18)(19)(20). 410 Our study is limited by the post-hoc design, which did not allow us to analyze the relationship of dietary protein and isoflavones alone to the IGF axis.…”
mentioning
confidence: 99%